Fertilization regime interacts with fall temperature in the nursery to determine the frost and drought tolerance of the Mediterranean oak Quercus ilex subsp. ballota - Heredia-Guerrero, Norberto; Oliet, Juan a; Villar-Salvador, Pedro; Benito, Luis F; Peñuelas, Juan L (Forest Ecology and Management, 2014)
Nitrogen fertilization in the nursery usually improves the transplanting performance of Mediterranean oaks. However, high N fertilization can reduce seedling stress tolerance, probably depending on the environmental conditions under which plants grow. We hypothesize that high N fertilization under mild fall conditions reduces cold and drought acclimation. To assess this hypothesis, we studied if fall temperature differences among cultivation locations influence the effect of N fertilization regime on cold and drought tolerance, N status and growth in the evergreen Mediterranean oak Quercus ilex subsp. ballota (Desf.) Samp. Plants were cultivated in two nurseries of distinct fall temperature conditions (mild and cold fall nurseries) under four fertilization regimes: Low and high N at constant rate (total N, 33 and 175mgseedling−1), high N at exponential rate (175mgNseedling−1) and fall N loading (89mgNseedling−1). Seedling water relations, survival to a −12°C frost and leaf soluble carbohydrates concentration were assessed three times in the fall, and shoot elongation was measured weekly through the fall. Moreover, seedling mass and N concentration were measured at the end of the fall. Fall loaded seedlings had the highest tissue N concentration, while seedling mass was highest in the high N constant and exponential fertilization regimes. Seedlings at the cold fall nursery concentrated more N but were smaller than seedlings at the mild fall nursery. Cessation of shoot elongation in the mild fall nursery occurred 1month later than in the cold location and high N exponentially-fertilized plants ceased shoot elongation later than the rest of fertilization treatments. Seedlings at the mild fall location had lower drought and cold tolerance than plants at the cold fall site. At mid fall, exponential fertilization at the mild nursery reduced seedling frost and drought tolerance, but treatment differences vanished at the end of the fall. In contrast, fertilization regime did not affect either cold or drought tolerance of seedlings at the cold fall nursery. Across dates and nurseries, frost survival was positively related to leaf soluble carbohydrates concentration and dry weight fraction. Beside, degree of cold acclimation decreased with shoot elongation cessation date and increased with leaf soluble carbohydrates concentration, suggesting a link between shoot growth activity, soluble carbohydrates, and frost tolerance. We conclude that Q. ilex subsp. ballota hardening is reduced by high N exponential fertilization mainly under mild fall conditions, while fall loading and constant low N fertilization did not affect hardening.
Keywords: Cold acclimation; Hardening; nitrogen; Nutrient loading; Osmotic potential; Soluble carbohydrate